Nanotechnology‐Assisted RNA Delivery: From Nucleic Acid Therapeutics to COVID‐19 Vaccines (Small Methods 9/2021). Issue 9 (14th September 2021) - Rinoldi, Chiara; Zargarian, Seyed Shahrooz; Nakielski, Pawel; Li, Xiaoran; Liguori, Anna; Petronella, Francesca; Presutti, Dario; Wang, Qiusheng; Costantini, Marco; De Sio, Luciano; Gualandi, Chiara; Ding, Bin; et al.
Abstract : Back Cover In article number 2100402, Pierini and co‐workers summarize recent advances in the development of nanotechnology‐mediated RNA delivery systems, which permits overcoming human body barriers and exploit the RNA biochemical functions at the target site. Researchers working in different fields have made enormous efforts to design RNA‐based therapeutics for treating severe medical conditions, revealing the potential clinical translation of RNA therapeutics.